2014
DOI: 10.1123/jsep.2014-0083
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Six Weeks of Sprint Interval Training on Mood and Perceived Health in Women at Risk for Metabolic Syndrome

Abstract: The purpose of this investigation was to determine whether 6 weeks of sprint interval training (SIT) is associated with changes in mood and perceived health in women at risk for developing metabolic syndrome (MetS). Physically inactive women (30-65 years) were randomized to 6 weeks of nutrition meetings and SIT (n = 23; 3 bouts/week of 4-8 30-s cycle sprints with 4-min recovery) or a nonexercise control condition (CON; n = 24). Before and after the 6-week intervention, perceived health status and mood were ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 23 publications
2
25
0
Order By: Relevance
“…This may (Frazão et al, 2016;Saanijoki et al, 2015), or may not (Freese et al, 2014;Jung et al, 2014) be the case for HIT protocols that rely on many (4-10) longer (30-60 s) sprints, but the ratings of perceived exertion in response to two 20-s sprints as used in the REHIT protocol in the present study appear to be manageable, and the majority of participants (12 out of 16) stated a preference for performing REHIT rather than the walking intervention based on current physical activity recommendations. There is therefore an urgent need to perform further studies examining the efficacy, acceptability, and longer-term adherence to REHIT as a practical 'real-life' intervention.…”
Section: Discussionmentioning
confidence: 99%
“…This may (Frazão et al, 2016;Saanijoki et al, 2015), or may not (Freese et al, 2014;Jung et al, 2014) be the case for HIT protocols that rely on many (4-10) longer (30-60 s) sprints, but the ratings of perceived exertion in response to two 20-s sprints as used in the REHIT protocol in the present study appear to be manageable, and the majority of participants (12 out of 16) stated a preference for performing REHIT rather than the walking intervention based on current physical activity recommendations. There is therefore an urgent need to perform further studies examining the efficacy, acceptability, and longer-term adherence to REHIT as a practical 'real-life' intervention.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of SIT have been explored in healthy populations (Hazell et al, 2014;Macpherson et al, 2011;Whyte et al, 2010), and in some clinical populations (Gibala et al, 2012). With regard to overweight/obese women who are underrepresented in the SIT literature, positive effects on aerobic capacity and cardiovascular function, post-exercise blood lipids, and perceived health status and mood have been reported (Freese et al, 2014;Freese et al, 2015;Trilk et al, 2011). While studies have shown that the benefits of SIT are similar to those of continuous exercise involving a greater volume of work in D r a f t different populations (Gist et al, 2013;Kessler et al, 2012), the feasibility of overweight/obese women adhering to these 'all out' efforts is unclear, as are the relative effects of the two types of training when energy expenditure during training is equal.…”
Section: R a F T D R A F T Introductionmentioning
confidence: 99%
“…Further, SIT has shown to improve motivation, particularly with regard to appearance and maintenance of body mass, as well as quality of life scores in elderly sedentary people (Knowles et al, 2015 ). Contradicting the assumptions made by Hardcastle et al ( 2014 ), results from a randomized controlled trial showed that 6 weeks of SIT lead to improvement in the perception of health and mood of sedentary women (30–65 years) at risk for metabolic syndrome (Freese et al, 2014 ).…”
mentioning
confidence: 99%